PENDEKATAN DALAM PENDIDIKAN ISLAM - Aini, Nafilah Nur; Lubis, Fitri (Proceeding International Seminar of Islamic Studies, 2024)
The approach to islamic education is one of the most important aspects of education. Why is an approach to islamic education one of the most important aspects of education, so that teachers can deepen the knowledge of what needs to be considered when teaching is accomplished. As for the research methods used in this journal are qualitative methods. Qualitative methods stemming from descriptive sources that researches quote some documented letters, library research, and researcher also cite from the Qur’an and as-Sunnah at their point of reference as a reference source in approaches to islamic education. And purpose of writing this journal is to dig deeper and more deeply related approaches in islamic education.